A Novel TAF-Related Signature Based on ECM Remodeling Genes Predicts Glioma Prognosis - Wang, Lin-jian; Lv, Peipei; Lou, Yongli (Frontiers in Oncology, 2022)
The composition and abundance of immune and stromal cells in the tumor microenvironment (TME) dramatically affects prognosis. Infiltration of immunosuppressive tumor-associated fibroblasts (TAFs) is a hallmark of glioma. However, the mechanisms regulating TAFs infiltration and the prognostic value of TAFs-related genes in glioma remain unclear. In this study, we analyzed TAFs infiltration by EPIC algorithm based on multiple glioma databases, including the TCGA GBMLGG cohort, the CGGA #325 cohort, and the CGGA #693 cohort. TAFs infiltration was increased in glioblastoma (GBM), and elevated TAFs infiltration predicted poorer survival in gliomas. Gene enrichment analyses revealed that differentially expressed genes (DEGs) between low grade glioma (LGG) and GBM were significantly enriched in the ECM remodeling related signaling, which may contribute to immune escape and resistance to Immune-Checkpoint Blockers (ICBs). To identify co-expression modules and candidate hub genes that may be associated with TAFs infiltration, we performed weighted correlation network analysis (WGCNA) of DEGs. Afterwards, univariate Cox regression, the least absolute shrinkage and selection operator (LASSO) regression and multivariate Cox regression analysis were performed to screen the positive prognostic hub genes. Finally, a high efficacy prediction signature was constructed based on the expression of PLAUR, EMP3 and S100A4. The signature correlated with the abundance of TAFs infiltration in glioma, and was an independent risk factor for glioma. In conclusion, our findings suggested that TAFs related signature was a valuable prognostic biomarker in glioma and provided potential targets for integrative therapy of gliomas.